CMP process optimization using alkaline bulk copper slurry on a 300 mm Applied Materials Reflexion LK system - 王辰伟 马锁辉 刘玉岭 陈蕊 曹阳 (Journal of semiconductors, 2013)
CMP process optimization for bulk copper removal based on alkaline copper slurry was performed on a 300 mm Applied Materials Reflexion LK system. Under the DOE condition, we conclude that as the pressure increases, the removal rate increases and non-uniformity is improved. As the slurry flow rate increases, there is no significant improvement in the material removal rate, but it does slightly reduce the WIWNU and thus improve uniformity. The optimal variables are obtained at a reduced pressure of 1.5 psi and a slurry flow rate of 300 ml/min. Platen/carrier rotary speed is set at a constant value of 97/103 rpm. We obtain optimized CMP characteristics including a removal rate over 6452 A/min and non-uniformity below 4% on blanket wafer and the step height is reduced by nearly 8000 A/min in the center of the wafer on eight layers of copper patterned wafer, the surface roughness is reduced to 0.225 nm.